El derecho digital y de las nuevas tecnologías: su importancia en el gobierno y en la empresa - Núñez Ponce, Julio (2021)
Digital Law and New Technologies has incidence and importance in the automated and global society, where the technological rhythm allows everyone in the world to use the new information and communication technologies. We proceed to the analysis of the different areas of application between Law and Technology: people, legal act, internet marriage, conciliation by electronic means, law of digital signatures and certificates, promotion of broadband, computer crimes. Likewise, the Digital Government Law and the Digital Government Law and the Digital transformation of the Judiciary are analyzed. The Digital Approach and Corporate Law section deals with the protection of personal data, teleworking, the tax impact of digital service and consumer protection in Electronic Commerce. The conclusions highlight the importance and significance of the discipline.